2016
DOI: 10.1242/jcs.190470
|View full text |Cite
|
Sign up to set email alerts
|

Upon Wnt stimulation, Rac1 activation requires Rac1 and Vav2 binding to p120-catenin

Abstract: There was an error published in J. Cell Sci. 125, 5288-5301.In Fig. 2B, panels labelled as the actin input and p120-catenin IP:p120-catenin panels were inadvertently assembled to show the same blots. Concerns were also raised about possible duplications and/or splices in Figs 4A, 4E, 5D, 6A and 6C. The authors were unable to obtain the original data in order to address these concerns and therefore repeated the experiments. The new data are shown in the figures below and have been verified by the corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…After induction of WNT signaling, p120 catenin dissociates from E-cadherin and recruits Kaiso into the nucleus 23 and activates Rac via Vav2. 25 Our results showing RhoH and Kaiso association and both cytosolic and nuclear co-localization in Jurkat cells after chemokine stimulation suggest that RhoH may form a complex with Kaiso and p120 catenin. To investigate this possibility, we determined the association of RhoH with p120 catenin in Jurkat cells.…”
Section: Rhoh and Kaiso Down-regulate F-actin Assembly And Cell Migramentioning
confidence: 57%
“…After induction of WNT signaling, p120 catenin dissociates from E-cadherin and recruits Kaiso into the nucleus 23 and activates Rac via Vav2. 25 Our results showing RhoH and Kaiso association and both cytosolic and nuclear co-localization in Jurkat cells after chemokine stimulation suggest that RhoH may form a complex with Kaiso and p120 catenin. To investigate this possibility, we determined the association of RhoH with p120 catenin in Jurkat cells.…”
Section: Rhoh and Kaiso Down-regulate F-actin Assembly And Cell Migramentioning
confidence: 57%
“…One possibility is that K547 ubiquitination interferes with the interaction between Ctnnd1 and Vav2. Vav2 is the GEF that promotes GTP binding to Rac1 (40,41), and interaction of Ctnnd1 with Vav2 promotes Rac1 activation (31,42). Therefore, Mib1-driven Ctnnd1 ubiquitination might inhibit the interaction of Ctnnd1 with Vav2, thereby reducing Rac1 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive atoh1a reduces fgfr1 expression and attenuates FGF signaling in the pLLP, resulting in the expansion of Wnt signal (21). Recently, Valls et al (42) showed that Wnt signal induces Rac1 activity via Ctnnd1 in HEK-293 cells, SW-480 cells, and Xenopus embryos. Therefore, in mib1 ta52b pLLP, the Rac1 activity level might be highly elevated owing to loss of Notchdependent signal in addition to the Mib1-Ctnnd1-Rac1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…5 Dephosphorylation of tyrosine residues 112 or 217 of p120 catenin augments cell migration during convergent extension in Xenopus. 15 In the preceding paper, we show that dephosphorylation of tyrosine residues 217 and 228 of p120 catenin-δ1-3A (CTNND1-3A) accomplishes the same in zebrafish embryos. 16 In cell cultures, the phosphorylation of p120 catenin is known to occur on six serine (S) and two threonine (T) residues in the N-and C-terminal regions, which include S122, S252, S268, S288, T310, S312, S879, and T916.…”
Section: Introductionmentioning
confidence: 88%